MOTIVATION OF THE ELDERLY TWIG ‘AISYIYAH RONOWIJAYAN PONOROGO PARTICIPATES IN ELDERLY GYMNASTICS IN MAINTAINING FITNESS - Shomat, Fauza Akbar; Sulistyarto, Soni (Riyadhoh : Jurnal Pendidikan Olahraga, 2023)
Seeing the phenomenon around the house where there is an association of elderly mothers who take part in the 'Aisyiyah Ronowijayan Branch Leadership organization and have an elderly gymnastic work program which is attended by many elderly people. The Leaders of the 'Aisyiyah Ronowijayan Ponorogo Branch held elderly gymnastics 2x a week, initially only once a week. Judging from the increase, it could be said that the elderly had an interest and interest in the elderly gymnastics held by the Leaders of the 'Aisyiyah Ronowijayan Branch. In the end, researchers were interested in examining the motivation of the elderly. Data for this quantitative descriptive study were collected through a questionnaire. This study involved 25 parents of the Branch Manager "Aisyiyah Ronowijayan Ponorogo", who were selected through a total sampling technique. The questionnaire used consisted of 35 statements. The results showed that the elderly members of the Aisyiyah Ronowijayan Branch Leadership as a whole had a level of motivation to take part in the lasia exercise in the "very high" category, with a percentage of 0% (0 elderly), the "low" category, with a percentage of 100% (25 elderly), and the "very low" category, with a percentage of 0% (0 elderly). With an average of 104.8, it can be concluded that the motivation of the elderly members of the Aisyiyah Ronowijayan Branch Leadership is in the "high" category.